IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN IMTAQ (IMAN DAN TAQWA) DI SMK TARUNA - Al Fiqri, Yanuar; Nuratika, Sagita; Nursila, Nursila (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The background of this research is the current situation of students with bad personalities.Therefore, there is a need for programs and activities that can develop and shape good character in all students.The program was initiated by Pekanbaru Tarna Vocational School and named Imtaq Program.The purpose of this study is to examine the practice of character education through Imtaq activities at Pekanbar Tarna Vocational School.The type of research used by the authors in this study is a field study using qualitative methods.Data collection techniques currently in use include observation, interview, and documentation methods.The subjects of this study were Islamic religious education teachers, IMTAQ coordinator members, and students.Based on the findings, it is clear that the implementation of her Imtaq Student Character Implementation Program at Pekan Baltarna Vocational School was successfully implemented in accordance with the program set by the school.The Imtaq program allows students to express good character traits.